Comportamento mecânico de concretos asfálticos com diferentes granulometrias, ligantes e métodos de dosagem - Almeida Júnior, Pedro Orlando Borges de (2016)
The degradation of the pavement has grown considerably due to the modification of traffic characteristics. It was increased the volume of traffic, the transported load and the tire inflation pressure, which added to the lack of load inspection on the load transport causes the asphalt coating the early appearance of defects. In order to seek progress on knowledge of the behavior of asphalt mixtures this study aimed to analyze the influence of the dosing method, of the granulometry and binders in the mechanical behavior of asphalt mixtures and determinate which of these three variables most influence on the mechanical behavior of the material. It was used two dosing method, Superpave and Marshall, four granulometries, two of them determined by Bailey method (range B and range C) and two by trial (range B and range C- simple framework on the ranges) and two type of asphalt binders: CAP 50-70 and the CAP 60-85, totalizing sixteen asphalt mixtures. The mixtures were evaluated in indirect tensile strength, stiffness in the resilient modulus testing and complex modulus, which used the 2SDP1D modeling to the composition of the master curves, and the permanent deformation by Flow Number test. The obtained results indicated that the factor that alter the stiffness and resistance to permanent deformation of the mixtures was the type of asphalt binder, wherein the modified binder increased the stiffness and damage resistance of the mixtures. The Bailey method of granulometric selection has also improved the behavior of the mixtures on a smaller scale of influence than the type of asphalt binder, followed by the dosing method Superpave that reduced the design binder content of the mixtures.